Time to Mohs Reconstruction: A Systematic Review Comparing Complication Rates between Immediate and Delayed Repair - Sciegienka, Sebastian; Slijepcevic, Allison; Lipsey, Kim; Spataro, Emily; Chen, Collin (Facial Plastic Surgery, 2023)
Several known factors affect outcomes of Mohs facial defect reconstruction; however, the effect of repair timing on outcomes is ill-defined. The aim of this study was to determine postoperative complication rates between immediate and delayed repair of Mohs facial defects. Preferred Reporting Items of Systematic Reviews and Meta-Analyses guidelines were used. Articles were selected using PICO format—population: Mohs facial defect patients, intervention: defect repair, comparator: immediate (<24 hours), or delayed (>24 hours) repair, outcome: complication rate. PubMed/Medline (1946-2020), EMBASE (1947-2020), Scopus (1823-2020), Web of Science (1900-2020), Cochrane Library, and Clinicaltrials.gov were searched. Two independent reviewers screened abstracts; those in English with human subjects reporting repair timing and complication rates were included. Search criteria yielded 6,649 abstracts; 233 qualified for review. Data were gathered from six studies; they alone contained comparative data meeting inclusion criteria. While many well-written studies were encountered, reported results varied widely. A statistically sound meta-analysis could not be completed due to large heterogeneity between studies, biasing the analysis towards the largest weighted study. Clinically important differences may exist between immediate and delayed Mohs reconstruction, but small study numbers, large heterogeneity, and lack of standardized outcome measures limit definitive conclusions. More studies are needed to perform appropriate meta-analyses, including studies using standardized methods of reporting Mohs outcome data.
Keywords: Mohs; reconstruction; time; outcomes